Kritik Atas The Moral Landscape: How Science Can Determine Human Values - Choirul Fuad Yusuf (Jurnal Lektur Keagamaan, 2013)
Moral value, or similarly termed as morality is the pivotal and crucial problem of human beings, since early history of civilization. In a debatable discourse of ethical concepts, Sam Harris through his work “The Moral Landscape: How Science Can Determine Human Values” formulated the new different concept of morality or moral values. He highlights that, in a reality, a science (natural science) has a full capacity which potentially determine human values, including toformulate moral judgment and moral conduct of human beings. Through his critical method, this article tries to describe and analyseSam Harris’s book on scientific morality and critisizing analytically from different perspectives. He highlighted that, in fact, the ideas of scientific morality--which is relative in nature--is not something new. Further, Harris’s theory of scientific morality which based on the scientific principles (rationality, positivity, and facticity), processually, is not perfectly capable of formulating “moral judgment” and “moral conduct” because of the nature of human being itself is multidimensional creature.Keywords: Morality, human values, scientific morality, moral judgment, moral conduct.